An ultrasonic-assisted chemical enhanced high shear low pressure grinding method
Patent Information
- Application Number
- CN202410928572.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-07-11
AI Technical Summary
[0003]本发明围绕当前晶体、陶瓷等难加工材料超精密磨粒加工易出现划痕、裂纹等损伤和加工效率低的问题,提出一种超声辅助化学增强高剪低压磨削方法
[0011]本发明的有益效果是:1、本发明所述的一种超声辅助化学增强高剪低压磨削方法,防弹衣式磨料磨具柔性紧密贴合超声振动的工件粗糙表面,有效避免法向应力集中,促进磨料、分散相和分散介质等磨料层组分在接触区域的充分均匀分布,加速工件粗糙表面化学反应生成软质钝化层。2、本发明所述的一种超声辅助化学增强高剪低压磨削方法,分散相和分散介质在超声空化效应下高效结合和聚集,形成增强型粒子簇,强化对磨料的把持力,高性能纤维在过渡层弹性变形和增强型粒子簇的冲击作用下,进一步提高磨料的剪切作用,以超声辅助化学增强高剪低压磨削方式高效去除软质钝化层时,不易对工件本体表面产生裂纹、划痕等损伤。
Smart Images

Figure CN118493095B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of precision and ultra-precision grinding technology, specifically relating to an ultrasonic-assisted chemically enhanced high-shear low-pressure grinding method. Background Technology
[0002] With the rapid development of modern technology, difficult-to-process materials such as crystals and ceramics are widely used in aerospace, weaponry, optical circuits, biomedicine and other fields. In order to achieve the industrial application standards of high-performance devices, ultra-precision abrasive processing such as grinding, lapping and polishing is usually required to obtain surfaces with atomic and near-atomic smoothness, near-damage-free subsurfaces and micron or even nanometer-level processing accuracy. However, ultra-precision abrasive processing usually faces huge challenges: (1) scratches, cracks, abrasive embedding and other damage are easy to occur, and even cracking may occur in areas with high normal stress concentration, affecting the service performance of materials; (2) the efficient low / no damage material removal behavior is complex, the stability of ultra-precision processing is poor, and the material removal efficiency is low. Patent application number 201710007909.3, entitled "A Grinding Method with High Tangential Grinding Force and Low Normal Grinding Force," proposes a grinding method based on a "bulletproof vest principle" that can remove workpiece surface material with high quality and ultra-precision. However, the abrasive layer composition of the specially designed grinding tool cannot be quickly, fully, and uniformly distributed in the contact area. Patent application number 202111540855.X, entitled "An Ultrasonic-Assisted High-Shear Low-Pressure Grinding Device and Method," proposes an ultrasonic-assisted high-shear low-pressure grinding device and method based on an industrial robot. This method can achieve force-controlled grinding of complex curved surface parts. However, during the grinding process, the micro-nano abrasive directly acts on the workpiece material, which easily causes surface / subsurface damage. Patent application number 201710222157.2, entitled "Mechanical-Chemical Grinding Method for Nanoscale Deep Damage Layers," provides a mechanical-chemical grinding method for low-damage ultra-precision machining of silicon wafers and glass. However, the grinding tool uses a self-made ceramic-based diamond grinding wheel, which is in direct rigid contact with the workpiece. This leads to stress concentration in the contact area, making it difficult to effectively avoid surface / subsurface damage. Therefore, aiming to eliminate surface scratches, cracks, and other damage, and improve surface quality and processing efficiency, this invention proposes an ultrasonic-assisted chemically enhanced high-shear low-pressure grinding method using a bulletproof vest-like grinding wheel for high-efficiency, high-quality ultra-precision machining. This method combines high-frequency ultrasonic vibration, flexible and tight contact, efficient chemical reaction, and high-shear low-pressure grinding behavior to promote workpiece surface modification, avoid normal stress concentration, improve tangential stress removal, and effectively improve workpiece surface quality and processing efficiency. This provides reliable technical support for the application of difficult-to-machine materials such as crystals and ceramics in various fields, further promoting innovation and development in related industries. Summary of the Invention
[0003] This invention addresses the problems of scratches, cracks, and low processing efficiency in the ultra-precision abrasive machining of difficult-to-machine materials such as crystals and ceramics. It proposes an ultrasonic-assisted chemically enhanced high-shear low-pressure grinding method. During ultrasonic-assisted chemically enhanced high-shear low-pressure grinding, a bulletproof abrasive tool flexibly and tightly adheres to the ultrasonically vibrating workpiece surface, causing a chemical reaction that generates a soft passivation layer. The ultrasonic cavitation effect promotes the formation of reinforced particle clusters from the dispersed phase and dispersion medium, which, combined with the holding effect of high-performance fibers, enhances the shearing force of the abrasive. The soft passivation layer is removed with high quality and efficiency using ultrasonic-assisted chemically enhanced high-shear low-pressure grinding, minimizing scratches and cracks on the workpiece body.
[0004] The grinding method provided by the present invention is an ultrasonic-assisted chemically enhanced high-shear low-pressure grinding method:
[0005] 1) Manufacturing a bulletproof vest-type abrasive tool that utilizes chemical-mechanical synergy for grinding. The bulletproof vest-type abrasive tool includes an abrasive layer, a transition layer, and a matrix layer. The abrasive layer is composed of abrasive, dispersed phase, dispersion medium, additives, and high-performance fibers. The additives include pH adjusters, oxidants, surfactants, complexing agents, and corrosion inhibitors. The abrasive, dispersed phase, dispersion medium, and additives are thoroughly mixed and uniformly distributed on the high-performance fibers. The transition layer is made of elastic rubber or silicone, and the matrix layer is made of 6061 aluminum alloy or 7075 aluminum alloy. The transition layer is located between the abrasive layer and the matrix layer and is bonded to the matrix layer with an adhesive. The abrasive layer is wrapped around the outside of the transition layer and fixed to the matrix layer by bolts.
[0006] 2) In ultrasonic-assisted chemically enhanced high-shear low-pressure grinding, the workpiece is clamped on a device with three-dimensional ultrasonic vibration. The bulletproof abrasive tool contacts and compresses the workpiece, and the abrasive layer flexibly adheres to the rough surface of the workpiece under ultrasonic vibration. The transition layer undergoes elastic deformation under the compression, which further tightens the abrasive layer to adhere to the rough surface of the workpiece, effectively avoiding normal stress concentration. Ultrasonic vibration promotes the full and uniform distribution of abrasive, dispersed phase, dispersion medium, and additives in the contact area. With the help of the flexible and tight adhesion of the abrasive layer and the full and uniform distribution of its components, the chemical reaction between the rough surface of the workpiece and the pH adjuster is accelerated, and a uniform soft passivation layer is generated efficiently.
[0007] 3) The high-shear, low-pressure grinding system drives the bulletproof vest-type abrasive to generate reciprocating linear or rotary motion with the workpiece, forcing the dispersed phase and dispersion medium in the contact area to move. The ultrasonic cavitation effect increases the intensity of the movement of the dispersed phase and dispersion medium, and the dispersed phase and dispersion medium efficiently combine and aggregate to form reinforced particle clusters, which strengthen the tangential holding force of the abrasive and improve the shearing effect of the abrasive on the workpiece. Under the elastic extrusion of the transition layer and the impact of the reinforced particle clusters, the high-performance fiber's weave structure undergoes slippage, rearrangement, or reorientation, absorbing energy to enhance structural strength and further improving the shearing effect of the abrasive. When the critical shear yield stress for removing the soft passivation layer is exceeded, the soft passivation layer is removed by a grinding method with a high ratio of tangential grinding force to normal grinding force.
[0008] 4) After the soft passivation layer is removed, the impact load disappears, the reinforcing particle clusters gradually dissipate, and the abrasive, dispersed phase, dispersion medium, and additives gradually return to a uniform distribution state. As ultrasonic-assisted chemical-enhanced high-shear low-pressure grinding proceeds, the exposed workpiece surface after the soft passivation layer is removed can continue to undergo chemical reactions to generate a new soft passivation layer. By repeating the above process, high-quality and high-efficiency ultrasonic-assisted chemical-enhanced high-shear low-pressure grinding of the rough surface of the workpiece can be achieved.
[0009] The abrasive is selected from oxide abrasives, carbide abrasives, diamond abrasives, or cubic boron nitride abrasives. For oxide abrasives, aluminum oxide, magnesium oxide, cerium oxide, yttrium oxide, or silicon dioxide are preferred. For carbide abrasives, silicon carbide, boron carbide, or zirconium carbide are preferred. The dispersed phase is selected from inorganic or organic particles. For inorganic particles, silicon dioxide or zinc oxide are preferred. For organic particles, hydroxypropyl distarch phosphate, polymethyl methacrylate, or polystyrene are preferred. The dispersion medium is selected from water-based, oil-based, or organic media. For water-based media, deionized water is preferred. For oil-based media, mineral oil or vegetable oil is preferred. For organic media, polyethylene glycol, polyacryl alcohol, or polypropylene are preferred. The high-performance fiber is selected from Kevlar fiber, ultra-high molecular weight polyethylene fiber, or carbon fiber.
[0010] pH adjusters can be either acidic or alkaline. Preferred acidic adjusters include hydrochloric acid, sulfuric acid, phosphoric acid, acetic acid, or lactic acid. Preferred alkaline adjusters include potassium hydroxide, sodium hydroxide, ammonia, sodium bicarbonate, or sodium metasilicate nonahydrate. Oxidizing agents can be hydrogen peroxide, potassium permanganate, manganese dioxide, or perchloric acid. Surfactants can be polyethylene ether, hexadecyltrimethylammonium bromide, or sodium dodecylbenzenesulfonate. Complexing agents can be citric acid, acetic acid, or chitosan oligosaccharide. Corrosion inhibitors can be benzisothiazolinone, potassium monoalkyl phosphate, or diethanolamine.
[0011] The beneficial effects of this invention are as follows: 1. The ultrasonic-assisted chemically enhanced high-shear low-pressure grinding method of this invention uses a bulletproof abrasive tool that flexibly and tightly adheres to the rough surface of the workpiece vibrating under ultrasonic vibration, effectively avoiding normal stress concentration and promoting the full and uniform distribution of abrasive layer components such as abrasive, dispersed phase, and dispersion medium in the contact area, thereby accelerating the chemical reaction on the rough surface of the workpiece to generate a soft passivation layer. 2. In the ultrasonic-assisted chemically enhanced high-shear low-pressure grinding method of this invention, the dispersed phase and dispersion medium efficiently combine and aggregate under the ultrasonic cavitation effect to form enhanced particle clusters, strengthening the holding force on the abrasive. Under the elastic deformation of the transition layer and the impact of the enhanced particle clusters, the high-performance fibers further enhance the shearing effect of the abrasive. When the soft passivation layer is efficiently removed by ultrasonic-assisted chemically enhanced high-shear low-pressure grinding, it is less likely to cause damage such as cracks and scratches on the surface of the workpiece. Attached Figure Description
[0012] Figure 1 This is a schematic diagram of the structure of a bulletproof vest-type mold.
[0013] Figure 2 This is a microscopic schematic diagram of the non-contact state during grinding.
[0014] Figure 3 This is a microscopic schematic diagram of the soft passivation layer formed after contact.
[0015] Figure 4 This is a microscopic schematic diagram of the removal of the soft passivation layer by enhanced particle clusters.
[0016] Figure 5 This is a microscopic schematic diagram of the state recovery after the soft passivation layer is removed.
[0017] In the figure: 1-Abrasive layer, 2-Transition layer, 3-Matrix layer, 4-Abrasive, 5-Dispersed phase, 6-Dispersion medium, 7-Additive, 8-High-performance fiber, 9-Workpiece, 10-Soft passivation layer, 11-Reinforced particle cluster, 12-Abrasive debris. Detailed Implementation
[0018] Example 1
[0019] 1) Lithium niobate crystals are subjected to ultrasonic-assisted chemically enhanced high-shear low-pressure grinding. The transition layer 2 is made of elastic rubber, the matrix layer 3 is made of 6061 aluminum alloy, the abrasive 4 is made of titanium dioxide, the dispersed phase 5 is made of silica, the dispersion medium 6 is made of polyethylene glycol, the additives 7 include the pH adjuster potassium hydroxide, the oxidant potassium permanganate, the surfactant cetyltrimethylammonium bromide, the complexing agent chitosan oligosaccharide and the corrosion inhibitor benzisothiazolinone, and the high-performance fiber 8 is made of Kevlar fiber.
[0020] 2) A bulletproof vest-type abrasive is manufactured by using chemical-mechanical synergy to remove surface materials from lithium niobate crystals. Titanium oxide, silicon dioxide, polyethylene glycol, potassium hydroxide, potassium permanganate, hexadecyltrimethylammonium bromide, chitosan oligosaccharide, and benzisothiazolinone are thoroughly mixed and evenly distributed on Kevlar fibers to form the abrasive layer 1 of the bulletproof vest-type abrasive. Elastic rubber is placed between the abrasive layer 1 and the 6061 aluminum alloy and is bonded to the 6061 aluminum alloy with an adhesive. The abrasive layer 1 is wrapped around the elastic rubber and fixed to the 6061 aluminum alloy by bolt locking.
[0021] 3) During ultrasonic-assisted chemically enhanced high-shear low-pressure grinding, lithium niobate crystals are clamped on a device with three-dimensional ultrasonic vibration. The bulletproof abrasive contactes and compresses the lithium niobate crystals. The abrasive layer 1 flexibly adheres to the rough surface of the ultrasonically vibrating lithium niobate crystals. The elastic rubber deforms under the compression, making the abrasive layer 1 even more tightly adhere to the rough surface of the lithium niobate crystals, effectively avoiding normal stress concentration. Ultrasonic vibration promotes the full and uniform distribution of titanium dioxide, silicon dioxide, polyethylene glycol, potassium hydroxide, potassium permanganate, hexadecyltrimethylammonium bromide, chitosan oligosaccharide, and benzisothiazolinone in the contact area. With the help of the flexible and tight adhesion of the abrasive layer 1 and the full and uniform distribution of its components, the chemical reaction between the rough surface of the lithium niobate crystals and the pH adjuster is accelerated, and a uniform potassium niobate soft passivation layer 10 is efficiently generated.
[0022] 4) The high-shear low-pressure grinding system drives the bulletproof vest-type grinding wheel to generate reciprocating linear or rotational motion with the lithium niobate crystal, forcing the silica and polyethylene glycol in the contact area to move. The ultrasonic cavitation effect increases the intensity of the movement of silica and polyethylene glycol, and silica and polyethylene glycol efficiently combine and aggregate to form reinforced particle clusters 11, which strengthen the tangential holding force of titanium dioxide and improve the shearing effect of titanium dioxide on lithium niobate crystal. Under the extrusion of elastic rubber and the impact of reinforced particle clusters 11, the Kevlar fiber's woven structure slips, rearranges, or reorients, absorbing energy to enhance structural strength and further improving the shearing effect of titanium dioxide. When the critical shear yield stress for removing the potassium niobate soft passivation layer 10 is exceeded, the potassium niobate soft passivation layer 10 is removed by grinding with a high ratio of tangential grinding force to normal grinding force.
[0023] 5) After the potassium niobate soft passivation layer 10 is removed, the impact load disappears, the reinforced particle cluster 11 gradually dissipates, and titanium oxide, silicon dioxide, polyethylene glycol, potassium hydroxide, potassium permanganate, hexadecyltrimethylammonium bromide, chitosan oligosaccharide and benzisothiazolinone gradually return to a uniform distribution state. As ultrasonic-assisted chemically enhanced high-shear low-pressure grinding proceeds, the exposed lithium niobate crystal body surface after removing the potassium niobate soft passivation layer 10 can continue to undergo chemical reactions to generate a new potassium niobate soft passivation layer 10. Repeating the above process, high-quality and high-efficiency ultrasonic-assisted chemically enhanced high-shear low-pressure grinding of the rough surface of lithium niobate crystal is achieved.
[0024] Example 2
[0025] 1) Sapphire is subjected to ultrasonic-assisted chemically enhanced high-shear low-pressure grinding. The transition layer 2 is made of elastic rubber, the matrix layer 3 is made of 6061 aluminum alloy, the abrasive 4 is made of cerium oxide, the dispersed phase 5 is made of silica, the dispersion medium 6 is made of polyethylene glycol, the additives 7 include pH adjuster sodium metasilicate nonhydrate, oxidant manganese dioxide, surfactant sodium dodecylbenzenesulfonate, complexing agent chitosan oligosaccharide and corrosion inhibitor potassium monoalkyl phosphate, and high-performance fiber 8 is made of ultra-high molecular weight polyethylene fiber.
[0026] 2) Manufacturing a bulletproof vest-type abrasive for removing sapphire surface materials using a chemical-mechanical synergy. Cerium oxide, silicon dioxide, polyethylene glycol, sodium metasilicate nonahydrate, manganese dioxide, sodium dodecylbenzenesulfonate, chitosan oligosaccharide, and potassium monoalkyl phosphate are thoroughly mixed and evenly distributed on ultra-high molecular weight polyethylene fibers to form the abrasive layer 1 of the bulletproof vest-type abrasive. Elastic rubber is placed between the abrasive layer 1 and the 6061 aluminum alloy and is bonded to the 6061 aluminum alloy with an adhesive. The abrasive layer 1 is wrapped around the elastic rubber and fixed to the 6061 aluminum alloy by bolt locking.
[0027] 3) During ultrasonic-assisted chemically enhanced high-shear low-pressure grinding, the sapphire is clamped in a device with three-dimensional ultrasonic vibration. The bulletproof abrasive contactes and compresses the sapphire, and the abrasive layer 1 flexibly adheres to the rough surface of the ultrasonically vibrating sapphire. The elastic rubber deforms under the compression, making the abrasive layer 1 even more tightly adhere to the rough surface of the sapphire, effectively avoiding normal stress concentration. Ultrasonic vibration promotes the full and uniform distribution of cerium oxide, silicon dioxide, polyethylene glycol, sodium metasilicate nonahydrate, manganese dioxide, sodium dodecylbenzenesulfonate, chitosan oligosaccharide, and potassium monoalkyl phosphate in the contact area. With the help of the flexible and tight adhesion of the abrasive layer 1 and the full and uniform distribution of its components, the chemical reaction between the rough surface of the sapphire and sodium metasilicate nonahydrate is accelerated, and a uniform soft passivation layer 10 composed of tetrahydroxyaluminate is efficiently generated.
[0028] 4) The high-shear low-pressure grinding system drives the bulletproof vest-type grinding wheel to generate reciprocating linear or rotary motion with the sapphire, forcing the silica and polyethylene glycol in the contact area to move. The ultrasonic cavitation effect increases the intensity of the movement of silica and polyethylene glycol, and silica and polyethylene glycol efficiently combine and aggregate to form reinforced particle clusters 11, which strengthen the tangential holding force of cerium oxide and improve the shearing effect of cerium oxide on sapphire. Under the extrusion of elastic rubber and the impact of reinforced particle clusters 11, the ultra-high molecular weight polyethylene fiber undergoes slippage, rearrangement or reorientation of its weave structure, absorbs energy to enhance structural strength, and further improves the shearing effect of cerium oxide. When the critical shear yield stress of the soft passivation layer 10 composed of tetrahydroxyaluminate is exceeded, the soft passivation layer 10 is removed by a grinding method with a high ratio of tangential grinding force to normal grinding force.
[0029] 5) After the soft passivation layer 10 is removed, the impact load disappears, the reinforcing particle cluster 11 gradually dissipates, and cerium oxide, silicon dioxide, polyethylene glycol, sodium metasilicate nonahydrate, manganese dioxide, sodium dodecylbenzenesulfonate, chitosan oligosaccharide and potassium monoalkyl phosphate gradually return to a uniform distribution state. As ultrasonic-assisted chemically enhanced high-shear low-pressure grinding proceeds, the exposed sapphire body surface after the removal of the soft passivation layer 10 can continue to undergo chemical reactions to generate a new soft passivation layer 10 composed of tetrahydroxyaluminate. Repeating the above process, high-quality and high-efficiency ultrasonic-assisted chemically enhanced high-shear low-pressure grinding of sapphire rough surfaces is achieved.
[0030] Example 3
[0031] 1) Ultrasonic-assisted chemically enhanced high-shear low-pressure grinding is performed on single-crystal magnesium oxide. The transition layer 2 is made of silicone, the matrix layer 3 is made of 7075 aluminum alloy, the abrasive 4 is made of silica, the dispersed phase 5 is made of hydroxypropyl distarch phosphate, the dispersion medium 6 is made of deionized water, the additives 7 include pH adjuster phosphoric acid, oxidant potassium permanganate, surfactant cetyltrimethylammonium bromide, complexing agent citric acid and corrosion inhibitor benzisothiazolinone, and high-performance fiber 8 is made of carbon fiber.
[0032] 2) Manufacturing a bulletproof vest-type abrasive for removing surface materials of single-crystal magnesium oxide using chemical-mechanical synergy. Silica, hydroxypropyl distarch phosphate, deionized water, phosphoric acid, potassium permanganate, hexadecyltrimethylammonium bromide, citric acid, and benzisothiazolinone are thoroughly mixed and evenly distributed on carbon fibers to form the abrasive layer 1 of the bulletproof vest-type abrasive. Silicone is placed between the abrasive layer 1 and the 7075 aluminum alloy and is bonded to the 7075 aluminum alloy with an adhesive. The abrasive layer 1 is wrapped around the outside of the silicone and fixed to the 7075 aluminum alloy by bolt locking.
[0033] 3) In ultrasonic-assisted chemically enhanced high-shear low-pressure grinding, single-crystal magnesium oxide is clamped on a device with three-dimensional ultrasonic vibration. The bulletproof abrasive contactes and compresses the single-crystal magnesium oxide. The abrasive layer 1 flexibly adheres to the rough surface of the ultrasonically vibrating single-crystal magnesium oxide. The silicone undergoes elastic deformation under compression, further tightening the abrasive layer 1 to adhere to the rough surface of the single-crystal magnesium oxide, effectively avoiding normal stress concentration. Ultrasonic vibration promotes the full and uniform distribution of silica, hydroxypropyl distarch phosphate, deionized water, phosphoric acid, potassium permanganate, hexadecyltrimethylammonium bromide, citric acid, and benzisothiazolinone in the contact area. With the help of the flexible and tight adhesion of the abrasive layer 1 and the full and uniform distribution of its components, the chemical reaction between the rough surface of the single-crystal magnesium oxide and phosphoric acid is accelerated, and a uniform magnesium phosphate soft passivation layer 10 is efficiently generated.
[0034] 4) The high-shear low-pressure grinding system drives the bulletproof vest-type grinding wheel to generate reciprocating linear or rotary motion with the single-crystal magnesium oxide, forcing the hydroxypropyl distarch phosphate and deionized water in the contact area to move. The ultrasonic cavitation effect increases the intensity of the movement of hydroxypropyl distarch phosphate and deionized water. The hydroxypropyl distarch phosphate and deionized water efficiently combine and aggregate to form reinforced particle clusters 11, which strengthen the tangential holding force on silicon dioxide and improve the shearing effect of silicon dioxide on single-crystal magnesium oxide. Under the extrusion of silicone and the impact of reinforced particle clusters 11, the woven structure of carbon fiber slips, rearranges, or reorients, absorbs energy to enhance structural strength, and further improves the shearing effect of silicon dioxide. When the critical shear yield stress for removing the magnesium phosphate soft passivation layer 10 is exceeded, the magnesium phosphate soft passivation layer 10 is removed by grinding with a high ratio of tangential grinding force to normal grinding force.
[0035] 5) After the magnesium phosphate soft passivation layer 10 is removed, the impact load disappears, the reinforced particle cluster 11 gradually dissipates, and silica, hydroxypropyl distarch phosphate, deionized water, phosphoric acid, potassium permanganate, hexadecyltrimethylammonium bromide, citric acid and benzisothiazolinone gradually return to a uniform distribution state. As ultrasonic-assisted chemical-enhanced high-shear low-pressure grinding proceeds, the exposed surface of the single-crystal magnesium oxide body after the removal of the magnesium phosphate soft passivation layer 10 can continue to undergo chemical reactions to generate a new magnesium phosphate soft passivation layer 10. Repeating the above process, high-quality and high-efficiency ultrasonic-assisted chemical-enhanced high-shear low-pressure grinding of the rough surface of single-crystal magnesium oxide is achieved.
[0036] The specific embodiments described above are merely illustrative or explanatory of the principles of the present invention and do not constitute a limitation on the scope of protection of the present invention. Therefore, any modifications, alterations, equivalent substitutions, equivalent structures, and equivalent process changes made to the present invention without departing from the principles and scope of protection described herein should be covered within the scope of protection of the present invention.
Claims
1. An ultrasonic-assisted chemically enhanced high-shear low-pressure grinding method, characterized in that: The method is implemented through the following steps: 1) Manufacturing a bulletproof vest-type abrasive tool that utilizes chemical-mechanical synergy for grinding. The bulletproof vest-type abrasive tool includes an abrasive layer (1), a transition layer (2), and a matrix layer (3). The abrasive layer (1) is composed of abrasive (4), dispersed phase (5), dispersion medium (6), additives (7), and high-performance fibers (8). The additives (7) include pH adjusters, oxidants, surfactants, complexing agents, and corrosion inhibitors. The abrasive (4), dispersed phase (5), dispersion medium (6), and additives (7) are thoroughly mixed and evenly distributed on the high-performance fibers (8). The transition layer (2) is made of elastic rubber or silicone, and the matrix layer (3) is made of 6061 aluminum alloy or 7075 aluminum alloy. The transition layer (2) is located between the abrasive layer (1) and the matrix layer (3) and is bonded to the matrix layer (3) by an adhesive. The abrasive layer (1) is wrapped around the outside of the transition layer (2) and fixed to the matrix layer (3) by bolt locking. 2) During ultrasonic-assisted chemical-enhanced high-shear low-pressure grinding, the workpiece (9) is clamped on a device with three-dimensional ultrasonic vibration. The bulletproof abrasive contacts and presses against the workpiece (9). The abrasive layer (1) flexibly adheres to the rough surface of the ultrasonically vibrating workpiece (9). The transition layer (2) undergoes elastic deformation under the pressing action, which further tightens the abrasive layer (1) against the rough surface of the workpiece (9), effectively avoiding normal stress concentration. Ultrasonic vibration promotes the full and uniform distribution of abrasive (4), dispersed phase (5), dispersion medium (6), and additives (7) in the contact area. With the help of the flexible and tight adhesion of the abrasive layer (1) and the full and uniform distribution of its components, the chemical reaction between the rough surface of the workpiece (9) and the pH adjuster is accelerated, and a uniform soft passivation layer (10) is generated efficiently. 3) The high-shear low-pressure grinding system drives the bulletproof vest-type abrasive and the workpiece (9) to generate reciprocating linear or rotational motion, which forces the dispersed phase (5) and dispersion medium (6) in the contact area to move. The ultrasonic cavitation effect enhances the intensity of the movement of the dispersed phase (5) and dispersion medium (6). The dispersed phase (5) and dispersion medium (6) combine and aggregate efficiently to form reinforced particle clusters (11), which strengthens the tangential holding force on the abrasive (4) and improves the shearing effect of the abrasive (4) on the workpiece (9). Under the elastic compression of the transition layer (2) and the impact of the reinforced particle clusters (11), the high-performance fiber (8) undergoes slippage, rearrangement or reorientation of its weaving structure, absorbs energy to enhance the structural strength, and further improves the shearing effect of the abrasive (4). When the critical shear yield stress of the soft passivation layer (10) is exceeded, the soft passivation layer (10) is removed by a grinding method with a high ratio of tangential grinding force to normal grinding force. 4) After the soft passivation layer (10) is removed, the impact load disappears, the reinforced particle cluster (11) gradually dissipates, and the abrasive (4), dispersed phase (5), dispersion medium (6), and additive (7) gradually return to a uniform distribution state. As the ultrasonic-assisted chemical-enhanced high-shear low-pressure grinding proceeds, the exposed surface of the workpiece (9) after the removal of the soft passivation layer (10) can continue to undergo chemical reaction to generate a new soft passivation layer (10). Repeat the above process to achieve high-quality and high-efficiency ultrasonic-assisted chemical-enhanced high-shear low-pressure grinding of the rough surface of the workpiece (9).
2. The ultrasonic-assisted chemically enhanced high-shear low-pressure grinding method according to claim 1, characterized in that: The abrasive (4) is selected from oxide abrasive, carbide abrasive, diamond abrasive or cubic boron nitride abrasive. The oxide abrasive is selected from alumina, magnesium oxide, cerium oxide, yttrium oxide or silicon dioxide. The carbide abrasive is selected from silicon carbide, boron carbide or zirconium carbide. The dispersed phase (5) is selected from inorganic particles or organic particles. The inorganic particles are selected from silicon dioxide or zinc oxide. The organic particles are selected from hydroxypropyl distarch phosphate, polymethyl methacrylate or polystyrene. The dispersion medium (6) is selected from water-based medium, oil-based medium or organic medium. The water-based medium is selected from deionized water. The oil-based medium is selected from mineral oil or vegetable oil. The organic medium is selected from polyethylene glycol, polyacryl alcohol or polypropylene. The high-performance fiber (8) is selected from Kevlar fiber, ultra-high molecular weight polyethylene fiber or carbon fiber.
3. The ultrasonic-assisted chemically enhanced high-shear low-pressure grinding method according to claim 1, characterized in that: The pH adjuster is selected from acidic or alkaline adjusters. The acidic adjuster is selected from hydrochloric acid, sulfuric acid, phosphoric acid, acetic acid or lactic acid. The alkaline adjuster is selected from potassium hydroxide, sodium hydroxide, ammonia, sodium bicarbonate or sodium metasilicate nonahydrate. The oxidant is selected from hydrogen peroxide, potassium permanganate, manganese dioxide or perchloric acid. The surfactant is selected from polyethylene ether, hexadecyltrimethylammonium bromide or sodium dodecylbenzenesulfonate. The complexing agent is selected from citric acid, acetic acid or chitosan oligosaccharide. The corrosion inhibitor is selected from benzisothiazolinone, potassium monoalkyl phosphate or diethanolamine.
Citation Information
Patent Citations
A grinding method with high tangential grinding force and low normal grinding force
CN106625037B
Mechanical and chemical grinding method for nanometer deep damage layer
CN107042467A
Grinding tool with high tangential grinding force and low normal grinding force
CN106737247A
Ultrasonic-assisted machining high-shear low-pressure grinding device and method
CN114102276A